Insurance Companies and the Efficiency of Financial Intermediation in Nigeria (American International Journal of Economics and Finance Research, 2019)
The study examined the relationship between insurance companies and financial intermediation in Nigeria. The insurance industry is a vital part of the entire financial system. Apart from commercial banks, insurance companies contribute significantly to financial intermediation of the economy. Despite the fact that insurance companies are vital part of Nigerian financial system, Nigerian insurance companies have been struggling to meet up with their objective of enhancing sound financial intermediation efficiency. The objective of this study is to examine the relationship between Total insurance claims and Total insurance Income, Total insurance expenditure in order to determine the impact of insurance companies on financial intermediation efficiency in Nigerian insurance sector.This study relied basically on secondary data which are obtained from Central Bank of Nigeria statistical bulletin (CBN) and National Insurance Commission (NAICOM) annual report.The method of data analysis employed to achieve the stated objective is multiple regression analyses. It was revealed that there exist a positive or strong correlation between the dependent variable and independent variable in the insurance efficiency equation. Independent variables has been found as an increasing function of Dependent variable, this means that there is an increase in the level at which insurance companies fulfil their customers claims. It was also discovered that the parameter of total insurance income and other insurance expenditure in relationship with total insurance claim is statistically significant. The study therefore recommends that policies should be formulated to address firm-specifics and macroeconomic fundamentals that will drive down the high wedge between total insurance claims and total insurance income to further strengthen the efficiency of financial intermediation which will impact positively on economic growth. The study also recommends that there is need to strengthen the supervisory framework to curb tendencies for rent seeking behaviour of insurance company’s management.